Vespa Pustaka: A Communication Medium for Community-Based Literacydriven Human Development in Cirebon - Ghina Amaliyah; Siti Khumayah; Farida Nurfalah (Journal of Social Research, 2026)
This study aimed to analyze the role of Vespa Pustaka as a communication medium for community literacy-based human development in Cirebon. The study employed a descriptive qualitative approach with data collected through in-depth interviews, participatory observations, and documentation. The research informants consisted of the founder of the Vespa Pustaka community, beneficiaries, and community partners. Data analysis was conducted using the Miles and Huberman model, which involved data reduction, data display, and conclusion drawing. The findings indicate that Vespa Pustaka functions as a non-formal literacy innovation capable of increasing reading interest, expanding access to knowledge, and encouraging community social participation through literacy activities in public spaces. The communication process integrates interpersonal communication, digital media, and community collaboration, thereby strengthening the diffusion of literacy values within the community. The innovation adoption process occurs gradually through the stages of knowledge, persuasion, decision, implementation, and confirmation. Furthermore, a social system based on mutual cooperation values and volunteer support strengthens the sustainability of activities, although challenges remain, including limited volunteer availability and weather-related constraints. In conclusion, Vespa Pustaka not only provides reading access but also serves as a communication medium for human development that contributes to strengthening literacy capacity and community participation in Cirebon.